2015
DOI: 10.3168/jds.2015-9983
|View full text |Cite
|
Sign up to set email alerts
|

Dried distillers grains with solubles do not always cause late blowing in baby Swiss cheese

Abstract: Late blowing in Swiss cheese, a result of unwanted gas production, is unacceptable to consumers and causes economic loss to manufacturers. Cheese processors have raised concerns that feeding dried distillers grains with solubles (DDGS) to cows leads to this defect, in part because of clostridial spores. We hypothesized that spores in DDGS would affect the quality of milk and baby Swiss cheese by promoting late-blowing defects. Thirty healthy multiparous and mid-lactation Holstein cows were fed total mixed rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…propensity for defects, and we did not see any splits. The findings are consistent with our previous research (Manimanna Sankarlal et al, 2015), where feeding full-fat DDGS did not affect the quality of baby Swiss cheese produced compared with feeding a conventional dairy ration without DDGS to lactating Holstein dairy cows.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…propensity for defects, and we did not see any splits. The findings are consistent with our previous research (Manimanna Sankarlal et al, 2015), where feeding full-fat DDGS did not affect the quality of baby Swiss cheese produced compared with feeding a conventional dairy ration without DDGS to lactating Holstein dairy cows.…”
supporting
confidence: 93%
“…Even though the Houck article was not published in a peer-reviewed journal, the article is read by farmers and processors, so the implications of the article are relevant. In our previous work, it was shown that DDGS did not contain spores, yet TMR, manure, milk, and cheese did contain gas-producing spores (Manimanna Sankarlal et al, 2015). The present work was undertaken in an environment known to harbor gas-forming spores to investigate whether cheese made from milk of cows fed RF-DDGS was more prone to defects than cheese made from milk of cows fed a TMR.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations